One-by-One or All-at-Once? Self-Reporting Policies and Dishonesty - Rilke, Rainer M.; Schurr, Amos; Barkan, Rachel; Shalvi, Shaul (Frontiers in Psychology, 2016)
Organizational monitoring relies frequently on self-reports (e.g., work hours, progress reports, travel expenses). A “one-by-one” policy requires employees to submit a series of reports (e.g., daily or itemized reports). An “all-at-once” policy requires an overall report (e.g., an annual or an overview report). Both policies use people’s self-reports to determine their pay, and both allow people to inflate their reports to get higher incentives, that is, to cheat. Objectively, people can cheat to the same extent under both reporting policies. However, the two policies differ in that the segmented one-by-one policy signals closer monitoring than the all-at-once policy. We suggest here that lie aversion may have a paradoxical effect on closer monitoring and lead people to cheat more. Specifically, reporting a series of segmented units of performance (allowing small lies) should lead to more cheating than a one-shot report of overall performance (that require one larger lie). Two surveys indicated that while people perceive the all-at-once policy as more trusting, they still expected people would be equally likely to cheat in both policies. An experiment tested the effects of the two reporting policies on cheating. The findings showed that contrary to the participants' intuition, but in line with research on lie aversion, the one-by-one policy resulted in more cheating than the all-at-once policy. Implications for future research and organization policy are discussed.